Discovering computers fundamentals : (Course Technology, Cengage Learning, 2011)
Discovering computers offers students a basic understanding of computers that they can take with them once this course is completed. The most important thing to me is being able to teach the most current information about computers because computers are used everywhere! discovering computers offers up-to-date information and provides my students with the basic understanding of computers that they need to be successful in their future.